Studi Pertumbuhan, Mortalitas, dan Tingkat Eksploitasi Ikan Selar Kuning, Selaroides leptolepis (Cuvier dan Valenciennes) di Perairan Pulau Bintan, Riau - Achmad Sudradjat (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The estimation on population parameters of yellowstriped trevally, Selaroides leptolepis through the analysis of monthly length-frequency distribution was carried out by analyzing sample collected in Bintan waters, Riau from March 1998 to February 1999. Length-frequency data were analyzed by FiSAT program. The results showed that Von Bertalanffy growth parameters, L∞, K and growth performance (Ø’) were 18.0 cm, 1.2 y־¹and 2.59, respectively. Recruitment pattern showed one peak of recruitment. The total mortality (Z) was 4.45 and exploitation rate (E) was 0.48. Estimate results of fishing mortality and exploitation rate were found to be presently above appropriate levels.